Bromidobis(1,10-phenanthroline-κ2N,N′)copper(II) dicyanamidate - Dmytro Rak; Zuzana Pravcová; Ivan Potočňák (Acta Crystallographica Section E, 2010)
The title compound, [CuBr(C12H8N2)2][N(CN)2], is formed of discrete [CuBr(phen)2]+ complex cations and uncoordinated [N(CN)2]− anions (phen is 1,10-phenanthroline). The Cu atom is five-coordinated in a distorted trigonal-bipyramidal geometry by two phen molecules and one bromide ligand, which coordinates in the equatorial plane at a distance of 2.5228 (4) Å and lying along with the Cu and the amide N atoms on a twofold rotation axis. The two axial Cu—N distances [1.9926 (15) Å] are slightly shorter than the two equatorial Cu—N bonds [2.0979 (15) Å]. The structure is stabilized by a weak C—H...N hydrogen bond, with a cyanide N atom of the dicyanamide ligand as an acceptor, and π–π interactions between nearly parallel phenyl and pyridine rings of two adjacent phen molecules [centroid–centroid distance = 3.589 (1) Å], and between π electrons of the dicyanamide anion and the pyridine ring [N...Cg(pyridine) = 3.511 (3) Å; C—N...Cg(pyridine) = 80.2 (2)°].